«Shuttle» translation as a method of formation of functional semantic groups and synonymous series in Russian and Belarusian languages - Kraskouski, Mikalai I. (Journal of the Belarusian State University. Philology, 2019)
The article discusses the technique of «shuttle» translation – method of formation and complement of parallel functional semantic group of closely related languages, of compiling and creating a series of synonymous and dictionaries of synonyms in closely related languages. We produced testing of the methodology on the basis of a specific language material – verbal group for perception in Russian and Belarusian languages. We formed two groups of Russian and Belarusian verbs for perception, revealed verbs for perception, are not fixed by dictionaries of synonyms A. P. Evgenieva and M. K. Klyshko, and proved the groundlessness of the absence of these verbs in the relevant entries.